Manganese oxides synthesized via microwave-assisted hydrothermal method: phase evolution and structure refinement - Neto, Roumanos Georges Dib [UNESP]; Macedo, Wagner Costa [UNESP]; Fernandes, José Diego [UNESP]; de Souza, Agda Eunice [UNESP]; Teixeira, Silvio Rainho [UNESP]; Rocha, Kleper de Oliveira [UNESP]; Longo, Elson (FapUNIFESP (SciELO), 2022)
Manganese oxides were synthesized during 40 min at 140 ºC via Microwave-Assisted Hydrothermal (MAH) method and treated at different temperatures in order to evaluate the phase evolution using structure refinement (Rietveld method). The samples obtained were heat treated at temperatures defined by means of thermal analysis (160 ºC, 480 ºC, 715 ºC, 870 ºC, 920 ºC and 1150 ºC) and analyzed by X-Ray Diffractometry (XRD), X-Ray Fluorescence (XRF), Fourier Transform Infrared (FTIR) spectroscopy, Raman scattering, UV-Vis absorption and Scanning Electron Microscopy (SEM). Structural characterizations allowed to identify five distinct phases: α-MnO2, Mn3 O4, Mn5 O8, Na2 Mn5 O10 and Na4 Mn9 O18 with weight percentages dependent on the heat treatment. The hausmannite structure (average crystallite size ranging from 28.9 nm to 99.1 nm) is present in all samples and go through various oxidation and reduction processes from 160 ºC to 1150 ºC without any major variation in the lattice parameters. Chemical characterizations identifies the presence of Na+ ions in all samples, either as substitution defects or as components of specific crystalline structures (Na2 Mn5 O10 and Na4 Mn9 O18), showing that the synthesized manganese oxides works as Na+ intercalation compounds, important materials for energy storage devices optimization. The results presented enables a better interpretation of the thermal and structural characteristics of manganese oxides synthesized via MAH.
Óxidos de manganês sintetizados pelo método hidrotermal assistido por micro-ondas: evolução de fase e refinamento de estrutura
Keywords: Hausmannite; Manganese Oxides; Microwave-Assisted Hydrothermal Method; Rietveld Refinement